Adaptation Initiative Project Guide 2014-2018 - Community Health and Social Services Network (CHSSN) (2018)
The CHSSN’s initiative to adapt health and social services is supported by an investment from Health Canada, through the Roadmap for Canada's Official Languages 2013–2018: Education, Immigration, Communities. This initiative is being undertaken in partnership with the Ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded in order to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English. The agreement also divided the roles and responsibilities among the CHSSN, the MSSS, and the health and social services agencies.

Adaptation Initiative Project Guide 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

Community Health Education Program (CHEP) 2018-2019 - Community Health and Social Services Network (CHSSN) (2019)
The CHSSN Community Health Education Program (CHEP) serves the urban, rural and remote English-speaking communities around the province of Quebec, providing health and social information and support via video conferencing through the RUIS (McGill) Telehealth system. Twenty community NPI networks funded under the CHSSN Network Partner Initiative (NPI) from across the province of Quebec participated, by attending the CHEP video conferences and by hosting a CHEP DVD viewing session. The following report highlights the Community Health Education Program (CHEP) activities for the period from April 1, 2018, to March 31, 2019.

L'initiative d'adaptation : guide des projets 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Partners for Better Care - Community Health and Social Services Network (CHSSN) (2020)
Keywords: Official Language Minority Community (OLMC)

Vitality - Community Health and Social Services Network (CHSSN) (2019)
Keywords: Official Language Minority Community (OLMC)

Who We Are - Community Health and Social Services Network (CHSSN) (2019)

2009-10 Annual Report - Leading English Education and Resource Network (LEARN) (2010)
In a province as vast as Quebec, and with schools and school boards scattered over an enormous geographic expanse, the notion of bringing people together to create a COMMUNITY of collaboration may appear daunting, if not impossible. In reality, when people share similar interests and common goals, those physical impediments can quickly disappear. This is especially true when the ultimate objective is the academic success of our children in elementary and high schools. LEARN’s focus is to serve as a catalyst and facilitator for the creation of communities of collaboration composed of educators, parents and students across the province. It is our organization’s objective to make every effort possible to get the well-intentioned forces within the English educational milieu together to share the wealth of knowledge and experience that resides there.

2013-2014 Annual Report of CLC Activities - Leading English Education and Resource Network (LEARN) (2014)
Keywords: Official Language Minority Community (OLMC)

Annual Report 2016-2017 - Leading English Education and Resource Network (LEARN) (2017)

Annual Report 2017-2018 : Leading the Way - Leading English Education and Resource Network (LEARN) (2018)

Annual Report 2018-2019 - Leading English Education and Resource Network (LEARN) (2019)

Annual Report 2019-2020 : Learning in the Next Decade of Education - Leading English Education and Resource Network (LEARN) (2020)

CLC Chronicles 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)

CLC Initiative Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2015)
Keywords: Official Language Minority Community (OLMC)

Community Learning Centres : Changing Lives and Communities Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2013)
This year the 37 Community Learning Centres across Quebec worked collaboratively with more than 700 local, regional, provincial, and national partners, to leverage in excess of $3 million of in-kind services and resources to serve their schools and communities. CLCs are doing more than just leveraging resources; they are changing lives and communities. They serve as a place for education and community development, and have become an important part of collaborative community change efforts. The stories and best practices highlighted in this annual report capture the essence of the initiatives being implemented by CLCs to achieve change and progress in English speaking communities across Quebec. Highlights of the activities undertaken in 2012-2013 begin with how one of our most important stakeholder groups, our teachers, are engaging with our initiative. The Community-Based Learning approach is just one example of the many strategies CLCs are adopting to impact students and develop a culture of lifelong learning. This year’s activities also included many examples of in-school and after-school activities in which CLC students are learning about incorporating healthy living options into their lives as well learning about aboriginal culture and building relationships between aboriginal and non-aboriginal communities. CLCs mobilize community and partner support to address current and important needs in our schools, including improving school climate and reducing bullying. Their activities for adults and seniors demonstrate to students that learning truly is a lifelong process. Engaging parents before their children have even entered school and continuing to find ways to connect and support parents throughout school life is an ongoing and important part of our work.

June 12, 2014 - Leading English Education and Resource Network (LEARN) (2014)

June 13, 2013 - Leading English Education and Resource Network (LEARN) (2013)

Provincial Resource Team Report 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)
Over the last ten years, English schools in Quebec have increasingly embraced the dual role of supporting student perseverance and contributing to the vitality of their English-speaking communities. With more than 80 schools and adult education centres across the province now part of the Community Learning Centre (CLC) network, it is evident that School Boards are adopting a new way of thinking about school and community partnerships. This “integrated focus on academics, services, supports and opportunities leads to improved student learning, stronger families and healthier communities. Schools become centers of the community”
Keywords: Official Language Minority Community (OLMC)

Rapport Annuel 2009-2010 - Leading English Education and Resource Network (LEARN) (2010)
Dans une province aussi vaste que le Québec, où les écoles et les commissions scolaires sont dispersées sur une immense étendue géographique, la notion de rassembler les gens pour en faire une COMMUNAUTÉ de collaboration semble un obstacle gigantesque, sinon insurmontable. Dans la réalité, les gens partagent des intérêts similaires et des objectifs communs et cette notion d’impossibilité physique s’estompe rapidement. Cette évolution est particulièrement vraie quand l’objectif ultime est la réussite scolaire de nos enfants au niveau des écoles élémentaires et secondaires. LEARN a pour objectif de servir de catalyseur et de facilitateur pour la création de communautés de collaboration réunissant les éducateurs, les parents et les élèves à l’échelle de la province. L’objectif de notre organisation est de déployer tous les efforts possibles pour réunir les forces positives du milieu éducatif anglophone afi n de contribuer au partage des connaissances et des expériences disponibles au sein de notre communauté.

Update - Leading English Education and Resource Network (LEARN) (2012)

Update - Leading English Education and Resource Network (LEARN) (2016)

Year-End Report - Leading English Education and Resource Network (LEARN) (2016)
The Leading English Education and Resource Network (LEARN) is a non-profit organization that serves the public, private, anglophone and aboriginal Youth and Adult Education sectors of Québec. We bring together the expertise and efforts of educators, students, parents and partners in our community to cultivate success for all learners.

Baseline Data Report 2009-2010 : Demographic Profiles of Quebec's English-speaking Communities by selected CSSS Territories - Pocock, Joanne; Warnke, Jan (Community Health and Social Services Network (CHSSN), 2010)
This document presents selected demographic characteristics of the English-speaking population of the CSSS territories in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI) of the Community Health and Social Services Network (CHSSN). The information presented is drawn from the 2006 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec's official language minoritty community.
Keywords: Official Language Minority Community (OLMC)